One-pot solvothermal synthesis of dual-phase titanate/titania nanoparticles and their adsorption and photocatalytic performances - Cheng, Yu Hua (2014)
Dual phase titanate/titania nanoparticles undergo phase transformation gradually with the increase of solvothermal synthesis temperature from 100 °C to 200 °C, and eventually are fully transformed into anatase TiO2. The crystal structure change results in the changes of optical absorption, sensitizer/dopant formation and surface area of the materials which finally affect the overall dye removal ability. Reactions under dark and light have been conducted to distinguish the contributions of surface adsorption from photocatalytic degradation. The sample synthesized at 160 °C (S160) shows the best performances for both adsorption under dark and photocatalytic degradation of methylene blue (MB) under visible light irradiation. The adsorption mechanism for S160 is determined as monolayer adsorption based on the adsorption isotherm test under dark condition, and an impressive adsorption capacity of 162.19 mg/g is achieved. For the photocatalytic application, this sample at 0.1 g/L loading is also able to degrade 20 ppm MB within 6 hours under the visible light (>420 nm) condition.